Biblical Integration in a Mathematics Classroom: Qualitative Research in a Senior High School - Kristiana, Tabita Gabriela; Winardi, Yonathan; Hidayat, Dylmoon (JOHME: Journal of Holistic Mathematics Education, 2017)
This article discusses to what extent mathematics teachers do Biblical integration in their class, explores the challenges that mathematics teachers face when they do or want to do Biblical integration, and explores the school’s expectation of Biblical integration for mathematics teachers with more clarity and intentionality. Research was conducted from September until October 2016. The research subjects were the curriculum coordinator, head of the Department of Mathematics, seven mathematics teachers, and 362 senior high students. The data collection techniques that were used were a semi-structured interview, and a questionnaire. The results of the research showed that the school’s expectation is that teachers should be able show how mathematics is capable of expressing truths about God’s work, God’s beauty, and God’s regularity because God created mathematics. All of the mathematics teachers modeled Biblical qualities. The challenges and obstacles that mathematics teachers were confronted with was that they had little time to find Biblical integration material, they did not have enough understanding, they had difficulty doing Biblical integration from the material, and the teachers were afraid that their explanations about Biblical integration would sound forced to students, especially non-Christian students.ABSTRAK BAHASA INDONESIA:  Artikel ini membahas sejauh mana guru matematika melakukan integrasi Alkitabiah di kelasnya, tantangan dan hambatan yang dihadapi oleh guru matematika saat mereka melakukan atau ingin melakukan integrasi Alkitabiah, dan untuk mencari tahu ekspetasi sekolah tentang integrasi Alkitabiah untuk guru matematika dengan lebih jelas dan mempunyai maksud. Penelitian ini dilakukan dari September sampai Oktober 2016. Subjek penelitian adalah kordinator kurikulum, kepala departemen matematika, tujuh guru matematika, dan 362 siswa sekolah menengah atas. Teknik pengumpulan data yang digunakan yaitu wawancara terencana-tidak terstruktur dan kuisioner. Hasil dari penelitian menunjukkan bahwa ekspetasi sekolah adalah bagaimana matematika mampu menjadi tempat untuk mengantarkan siswa mengenal kebenaran seperti pekerjaan Tuhan, keindahan Tuhan, keteraturan Tuhan karena Tuhan menciptakan matematika. Kemudian, semua guru matematika menjadi contoh kualitas Alkitabiah. Hambatan dan tantangan yang dihadapi guru matematika adalah kekurangan waktu untuk menemukan integrasi Alkitabiah dari materi, mereka juga tidak mempunyai pemahaman yang cukup, mereka merasa kesulitan dalam melakukan integrasi Alkitabiah, dan guru merasa takut jika penjelasannya tentang integrasi Alkitabiah terdengar memaksa bagi siswa, terkhusus siswa yang beragama lain.